From Insult to Estrangement and Injury: The Violence of Racist Police Jokes. (November 2019) - Pérez, Raúl; Ward, Geoff
This article examines racially derogatory police jokes, what we call "racist blue humor, " as discourse that negatively targets and ridicules racial and ethnic minorities as inferior, dangerous, or as objects of symbolic and cultural violence. We argue that racist blue humor fosters the social acceptability of prejudice and discrimination among officers, normalizing a culture of dehumanization that legitimizes structural and direct violence. We analyze illustrative cases of racist blue humor in the light of critical race theory, humor studies, and other work in behavioral science to elaborate this violence and its potential for harm across multiple contexts. Racist blue humor engenders legal estrangement, diminishes protection and representation in law, and heightens exposure to police and other state violence. We conclude with considerations for research and policy, including order-maintenance policing of racist blue humor.